Differential uptake of recent Papanicolaou testing by HPV vaccination status among young women in the United States, 2008–2013. Issue 4 (August 2015) - Sauer, Ann Goding; Jemal, Ahmedin; Simard, Edgar P.; Fedewa, Stacey A.
Highlights: Women who had not initiated HPV vaccination less likely to have recent Pap test. Overall observation was consistent across most sociodemographic factors. Asians/others without HPV vaccine less likely than Whites to have recent Pap test. Abstract: Background: A positive association between recent Papanicolaou (Pap) test uptake and initiation of HPV vaccination among U.S. women has been reported. However, it is unknown whether recent Pap testing by HPV vaccination status varies by race/ethnicity. Discerning racial/ethnic variations is important given the higher prevalence of HPV types other than 16 and 18 in some racial/ethnic groups. We assessed whether uptake of recent Pap testing differed among women aged 21–30 years who had not initiated the HPV vaccination series versus those who had and whether this pattern differed by sociodemographic factors. Methods: 2008, 2010, and 2013 National Health Interview Survey data were used to generate weighted prevalence estimates and 95% confidence intervals (CIs) ( n = 7095). Adjusted predicted marginal models were used to generate adjusted prevalence ratios (aPRs) to assess the relationship between recent Pap test uptake and HPV vaccination series initiation by race/ethnicity. Results: The uptake of recent Pap testing among those who had not initiated the HPV vaccination series was significantly lower (81.0%) compared to those who had initiated vaccination (90.5%) (aPR = 0.93, 95% CI: 0.90–0.96). This finding was consistent across most sociodemographic factors, though not statistically significant for Blacks, Hispanics, those with lower levels of education, or those with higher levels of income. Conclusion: Young women who had not initiated HPV vaccination were less likely to have had a recent Pap test compared to women who had initiated vaccination. Concerted efforts are needed to increase uptake of recommended cervical cancer screening and HPV vaccination among young women.